Qualidade físico-química e armazenamento pós-colheita de frutos de genótipos de lima ácida Tahiti - Guilmo, Leonardo da Silva (Universidade Federal de São Carlos, 2022)
The Brazilian citrus industry is among the largest in the world, with a consolidated and growing market, with this, the demand for quality fruits for the domestic market and, mainly, for export, has been increasing. In BAG Citros IAC there are 23 accessions of acid lime (Citrus latifolia), the species has been exploited internationally as an “in natura” fruit, exported in large quantities by Brazil, especially to the European continent, but other alternatives for use for domestic market are concentrated juices, the main use of acid lime in Brazil, presenting high added value and with high investments. The objective of this work was to select genotypes of Tahiti acid lime (Citrus latifolia) in terms of vegetative development and productivity, physicochemical characteristics and post-harvest storage of the fruits. Initially, 12 acid lime genotypes were evaluated (IAC 304/IAC 5, IAC 616/IAC 10, BRS Ponta Firme, IAC 302, IAC 1728, IAC 654, CNPMF 02 IAC 1491, IAC 303, Folha Murcha IAC, Quebra Galho Catanduva, Quebra Galho Mogi Mirim and Quebra Galho Paranapuã) regarding the vegetative and productive development, and physicochemical characteristics of the fruits (Experiment 1). Subsequently, three genotypes were selected for evaluation of productive development and post-harvest testing, where the fruits were divided into standards for commercialization in the domestic and foreign markets (Experiment 2). The evaluations started in the second half of 2019 and ended in the second half of 2021. The genotypes IAC 304/IAC 5, IAC 616/IAC 10 and BRS Ponta Firme showed greater vegetative and productive development in March (2020), in addition, presented good results, staying within established standards for mass, conformation index, juice yield, vitamin C, total soluble solids, titratable acidity, ratio and technological index. In experiment 2, the IAC 616/IAC 10 and BRS Ponta Firme genotypes showed higher productivity compared to the IAC 304/IAC 5 genotype, in March (2021); and in the post-harvest test were also highlights, for fruits with standards for domestic and foreign markets, with less loss of mass and less loss of dark green color. There were no significant differences between genotypes for juice yield, vitamin C, soluble solids, acidity and ratio. Of the genotypes studied, IAC 616/IAC 10 and BRS Ponta Firme showed higher productivity and good results for physical-chemical analysis and post-harvest testing, showing potential to be new commercial varieties for Brazilian citrus industry.
Physicochemical quality and postharvest storage of fruits of Tahiti acid lime genotypes
Keywords: Citrus latifolia; Potencial produtivo; Mercado; Productive potential; Market; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA